Cleavage Stage versus Blastocyst Stage Embryo Transfer in Oocyte Donation Cycles - George Kontopoulos; Mara Simopoulou; Ioannis Zervomanolakis; Thomas Prokopakis; Kostas Dimitropoulos; Evaggelos Dedoulis; Stylianos Grigorakis; Kristi Agapitou; Eros Nikitos; Anna Rapani; Nikos Vlahos (Medicina, 2019)
Background and Objective: During the last few years, a trend has been noted towards embryos being transferred at the blastocyst stage, which has been associated with improved rates regarding implantation and clinical pregnancy in comparison to cleavage stage embryo transfers. There is a limited number of studies investigating this notion in oocyte donation cycles employing cryopreserved embryos. The aim of this study is to evaluate the implantation potential and clinical pregnancy rates between the day 3 cleavage stage and blastocyst stage embryo transfers in oocyte donation cycles employing vitrified embryos. Methods: This is a retrospective evaluation of oocyte donation frozen−thawed transfers completed in our clinic from January 2017 to December 2017. Intracytoplasmic sperm injection was conducted for all oocytes. Following fertilization, all embryos were cryopreserved either at the cleavage or blastocyst stage. Embryo transfer of two embryos was performed under direct sonographic guidance in all cases. Results: Our results confirmed a 55.6% clinical pregnancy (CP) resulting from day 3 embryo transfers, a 68.8% CP from day 5, and 71.4% CP from day 6. Significantly improved pregnancy rates were related to embryo transfers at the blastocyst stage when compared to cleavage stage transfers (68.9% and 55.6% respectively, p = 0.016). The risk with regards to multiple pregnancies was similar. Conclusion: Our findings indicate that in oocyte donation cycles employing vitrified embryos, embryo transfer at the blastocyst stage is accompanied with a significant improvement in pregnancy rates and merits further investigation.